Neutron flux monitoring with in-vessel fission chambers to detect an inadvertent control rod withdrawal in a sodium-cooled fast reactor. (August 2016) - Verma, V.; Filliatre, P.; Hellesen, C.; Jacobsson Svärd, S.; Jammes, C.
Highlights: In-vessel, ex-core fission chambers used to monitor neutron flux profile from IRW. Tapered tunnel introduced in lateral shield to provide increased detector signal. Possible to detect withdrawal of outer control rod in the core. Radial monitoring needed to precisely know the location of perturbation in core. Suggested use of in-core detectors coupled with peripheral fission chambers. Abstract: The neutron flux monitoring system forms an integral part of the safety design of a Generation IV sodium-cooled fast reactor. During the initial design phase of the neutron flux monitoring system, one needs to explore various detector locations and configurations. Diverse possibilities of the detector system installation should be studied for different locations in the reactor vessel in order to detect any perturbations in the core. In this paper, we investigate the possibility of placing fission chambers beyond the lateral neutron shield, ex-core but in-vessel and study the detectability of an inadvertent control rod withdrawal with these fission chambers. A generic core design of a Generation IV 1500 MWth French sodium-cooled fast reactor is used for the study, and calculations are performed with the Monte Carlo code SERPENT2. We propose certain design changes that are needed to be incorporated, w.r.t. the facilitation of neutron transport to this ex-core location. We are able to show that there is a detectable signature in the fission chambers following an inadvertent control rod withdrawal in the core. The equally-spaced azimuthal detectors are able to follow changes in the neutron flux distribution in the core. This study helps us to analyze multiple detector locations and give the general trends for monitoring indications to detect any perturbations in the core.